Evaluation of Adaptation and Production of Three Selected Cassava (Manihot esculenta Crantz) in Peat Land Area of Central Kalimantan - Fitriani, Hani; Hartati, N. Sri; Sudarmonowati, Enny (Jurnal ILMU DASAR, 2019)
Along with the increasing the of the land-use change of the fertile agricultural land in Java, the better awareness has been subjected to the importance of function peat land for agricultural development. Cassava (Manihot esculenta Crantz) is a tuber plant that potentially developed as important carbohydrate source. The objective of this research was to identify superior cassava variety candidate of selected cassava developed by of Research Centre Biotechnology, LIPI which has high adaptation capability and yield in Central Kalimantan peat land area. This research was conducted from July 2010 through May 2011 in Central Kalimantan Province (Kalampangan dan Pulang Pisau in total of area 1.5 and 2.25 ha respectively). There were three genotypes of cassava tested, i.e. Iding (high amylose), Gebang (low amylose), and Menti (high starch) compared to Adira 4 (35 ton/ha) and Darul Hidayah (102.1 ton/ha). The variables observed were plant height (cm) and tuber weight (grams). Observations were conducted at the age of 10 months. Data was analyzed using SPSS version 16.0. The results showed that the plant height and yield were higher in Pulang Pisau than Kalampangan even though the difference is not significant (P ≤ 0,05). Darul Hidayah has highest plant height and yield, 229.8 cm and 2271 g respectively among other genotypes/varieties grown at Pulang Pisau even though the value was not significant, whereas in Kalampangan, Darul Hidayah showed the lowest yield (670 g). Based on the data obtained, the Darul Hidayah variety can be cultivated by farmers in Pulang Pisau peat land to fulfill the availability of superior cassava seedlings for food, feed and industry. Keywords: Peat, tuber yield, plant height, liquid organic fertilizer, yam wood.